Transformation of distribution logistics management in the digitalization of the economy - Alexander Parfenov; Lubov Shamina; Jiahui Niu; Vladimir Yadykin (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
A problem predicted by experts with the onset of the COVID-19 pandemic is that many markets, in particular, the restaurant market, the tourism market, and the entertainment market, will face long-term stagnation in the near future due to outflow of financial resources. On the other hand, even though the standards of social interactions have changed, the basic needs of modern society for nourishing and varied food, entertainment and experiences cannot disappear as a result of a pandemic. The goal of our study consisted of gaining insights into the new hybrid practices of logistics and customer services that business needs to master in the new environment, combining offline and online activities. We have found that success in the market is achieved by organizations that regularly generate new entrepreneurial, scientific and technical ideas and consolidate their own and attracted resources to create, develop and launch new products, services and technologies on the market. Employing analytical methods, we have characterized the drivers of the transformation of distribution logistics management in the context of the digitalization of the economy, concluding that this process primarily affects the management of distribution channels. The features of transformation in the management of international distribution channels are studied. The requirements for logistics management in this functional area of management are defined.
Keywords: 650; digitalization; distribution; e-wholesale; logistics; omnichannel; sustainable development